Review of Denmark's Program for Better Business Regulation - International Finance Corporation; Multilateral Investment Guarantee Agency; World Bank (Washington, DC, 2017)
The report is organized as follows: the executive summary (I) pulls together all major conclusions and recommendations of the report. The following five sections then focus on key requirements of any successful regulatory reform program: (II) business regulation policy, (III) measurements and Targets, (IV) organization and procedures, (V) incentives for reform, and (VI) communication of results. Sections I-VI focuses on regulatory reform impacting directly on the private sector. The final section (VII) broadens the discussion and highlights potential benefits of further consolidating and integrating other regulatory reform efforts into a broader and coherent policy for regulatory quality and reform. Two annexes provide more details on two aspects of particular importance for the Danish regulatory reform program after 2010: measuring broader impacts of existing regulation, and regulatory advisory bodies.